Managing and motivating academic advisory boards in animal health for high performance - Adams, A. Paige; Stuteville, Rebekkah; Wolfe, Benjamin A. (Frontiers in Education, 2025)
IntroductionAcademic leaders and faculty in professional academic programs often gather input from practitioners to test the relevance of academic curricula. Program advisory boards for professional programs are established to provide feedback on curricula and industry needs; however, there is limited research examining the management of these boards. Although there exists research on managing volunteers in non-profit organizations and managing boards of directors, academic advisory boards occupy a position between informal volunteer arrangements and formal boards of directors with oversight responsibilities. The objective of this project was to use existing research on volunteer and board of director management to understand the experience of three academic advisory boards that provide advice and guidance on animal health academic programs.MethodsTwo surveys were administered to existing advisory boards at Kansas State University’s Olathe, Kansas Campus. The survey questions were aimed at determining the strengths and weaknesses of the campus’s academic advisory board recruitment and management practices using evidence-based practices for effective volunteer management.ResultsThe study’s findings suggest that the primary motivation for serving on an academic advisory board is a strong desire to contribute to the mission and vision of the institution. Several tactics emerged for engaging board members, including developing strong leadership in setting purpose and objectives, creating space for members to participate in dialogue in strategy, and assigning tasks that align with their knowledge, skill set, and network.DiscussionBest practices from this study demonstrate meaningful approaches to engage advisory boards so that volunteers feel more valued in how they can positively impact the future of educational programming.